1965
DOI: 10.1515/znb-1965-0714
|View full text |Cite
|
Sign up to set email alerts
|

Kombination synthetischer Insulinketten zu biologisch aktiven Präparaten

Abstract: Äquimolare Mengen synthetischer Insulin-Α- und -B-Kette wurden in flüssigem Ammoniak durch Natrium gemeinsam von Schutzgruppen befreit und zu einem Präparat mit 0,2 — 1,0% Insulinaktivität oxydiert. Dessen biologische Wirksamkeit wurde durch Insulin-Antiserum vollständig gehemmt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

1966
1966
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…The exhibit consists of written explanations, plots of the structure of insulin, small samples of some of the larger A and B chain peptides and the laboratory diary of Bremer with handwritten entries on all steps of his synthesis of the complete A chain, the combination with the synthetic B chain of Schnabel and Meienhofer and the data on the biological activity [56]. Strictly speaking, the first insulin syntheses were already outdated in 1974 when Rittel and his associates published their total synthesis of human insulin involving directed formation of the three disulfide bonds at different stages of the fragment-condensation approach [57].…”
Section: Thinking Back To My Early Research Workmentioning
confidence: 99%
“…The exhibit consists of written explanations, plots of the structure of insulin, small samples of some of the larger A and B chain peptides and the laboratory diary of Bremer with handwritten entries on all steps of his synthesis of the complete A chain, the combination with the synthetic B chain of Schnabel and Meienhofer and the data on the biological activity [56]. Strictly speaking, the first insulin syntheses were already outdated in 1974 when Rittel and his associates published their total synthesis of human insulin involving directed formation of the three disulfide bonds at different stages of the fragment-condensation approach [57].…”
Section: Thinking Back To My Early Research Workmentioning
confidence: 99%
“…With the knowledge of the aforementioned facts, it is not surprising that Zahn et al obtained a product of 0.2-1.0% insulin activity after a treatment of 1.5 h with sodium. 68 Several types of apparatus were developed for accomplishment of the sodium-liquid ammonia reduction.87,105,130 In a liquid ammonia apparatus containing a weighed amount of dissolved sodium, the compound to be reduced was added until the blue color just disappeared. 130 Another glass apparatus was mentioned in Section III.…”
Section: B the End Point And Duration Of The Reductionmentioning
confidence: 99%
“…However, by 1960 it was shown that active insulin could be reformed from inactive mixtures of reduced A and B chains by oxidation (58), and this observation stimulated peptide chemists throughout the world to attempt synthesis of the total hormone by synthesizing the separate A and B chains and combining them (137,149,338). Although it at first seemed to be a rather inefficient approach, yielding only a low percentage of correctly folded and oxidized insulin, further experimentation led to rapid advances such that by 1966 ylelds in excess of 50% were attained, based on the limiting concentration of the S-sulfonated B chain (the A chain was usually supplied in excess in its fully reduced form) (137).…”
mentioning
confidence: 99%